(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper, an evolutionary approach based Genetic algorithm, is adopted to find the initial seeds of K-means for compressing images. Genetic Algorithm is a kind of optimization technique inspired by the natural process of evolution, well suited to find true and approximate solutions for hard problems even with little knowledge of search space. The proposed method shows enhanced performance in terms of image quality , when applied to test images.